Стенд физического подобия «Тепловой объект»; Современные проблемы машиностроения - Федоренко Д. В.; Филипас А. А. Александр Александрович; Суходоев М. С. Михаил Сергеевич; Курганов В. В. Василий Васильевич; Павловский А. Александр (2025, 2025)
Текстовый файл